Whole Genome Sequencing Reveals Potential New Targets for Improving Nitrogen Uptake and Utilization in Sorghum bicolor - Massel, Karen; Campbell, Bradley C.; Mace, Emma S.; Tai, Shuaishuai; Tao, Yongfu; Worland, Belinda G.; Jordan, David R.; Botella, Jose R.; Godwin, Ian D. (Frontiers in Plant Science, 2016)
Nitrogen (N) fertilizers are a major agricultural input where more than 100 million tons are supplied annually. Cereals are particularly inefficient at soil N uptake, where the unrecovered nitrogen causes serious environmental damage. Sorghum bicolor (sorghum) is an important cereal crop, particularly in resource-poor semi-arid regions, and is known to have a high NUE in comparison to other major cereals under limited N conditions. This study provides the first assessment of genetic diversity and signatures of selection across 230 fully sequenced genes putatively involved in the uptake and mobilization of N from a diverse panel of sorghum lines. This comprehensive analysis reveals an overall reduction in diversity as a result of domestication and a total of 128 genes displaying signatures of purifying selection, thereby revealing possible gene targets to improve NUE in sorghum and cereals alike. A number of key genes appear to have been involved in selective sweeps, reducing their sequence diversity. The ammonium transporter (AMT) genes generally had low allelic diversity, whereas a substantial number of nitrate/peptide transporter 1 (NRT1/PTR) genes had higher nucleotide diversity in domesticated germplasm. Interestingly, members of the distinct race Guinea margaritiferum contained a number of unique alleles, and along with the wild sorghum species, represent a rich resource of new variation for plant improvement of NUE in sorghum.